Optimized extraction, quality characterization of Nagpur mandarin (Citrus reticulata) peel pectin - Kumar, Dinesh; Ladaniya, M S; Mendke, Sachin; Gurjar, Manju; Kumar, Sunil (The Indian Journal of Agricultural Sciences, 2020)
Nagpur mandarin (Citrus reticulata Blanco) is composed of 50-55 g peel per 100 g fresh fruit which is discarded as waste during processing. Pectin was extracted from fresh peel of Nagpur mandarin at ICAR- Central Citrus Research Institute, Nagpur, Maharashtra, India (2016-17) using four different methods. Pectin yields varied from 1.70-2.80% on dry weight basis. The extraction condition using pre-treatment (Blanching at 74ºC for 10 mins), double extraction method from fresh peel gave better yield. The isolated pectin contained 69.35% anhydrouronic acid (AUA), equivalent weight of 694.44, methoxyl content 6.57%, 56.33% degree of esterification and jelly grade 160. Purification using alcohol precipitation followed by acetone wash was effective to yield pectin of high purity. According to the values of methoxyl content and degree of esterification, pectin isolated from Nagpur mandarin peels can be classified as high methoxyl content (HMP) and has potential industrial use in manufacture of value added products.